Reinforcing Public University Student’s Worship Education by Developing and Implementing Mobile-Learning Management System in the ADDIE Instructional Design Model - Hanafi, Yusuf; Murtadho, Nurul; Ikhsan, M. Alifudin; Diyana, Tsania Nur (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This study aimed to develop and investigate the impact of the implementation of the Mobile-Learning Management System, which we call elektronik Bimbingan Baca al-Qur’an (e-BBQ, a word in the Indonesian Language), in fostering student’s worship. This research was conducted at Universitas Negeri Malang in the odd semester of the 2018-2019 academic year with ADDIE research design. The implementation stage was carried out with a one-group pretest-posttest design. As a result, the e-BBQ developed was in the form of applications and websites with some menus including Al-Qur’an learning, worship, training, and log in instructor. The evaluation by experts, as well as students and instructors showed that the products developed were suitable for use. e-BBQ has a positive effect; the quality of student’s worship increased significantly after participating in learning by utilizing e-BBQ. e-BBQ is considered to be an interesting medium for learning Islamic religion, able to make learning more enjoyable, and raise the student’s learning motivation